The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s10342-005-0106-2
|View full text |Cite
|
Sign up to set email alerts
|

The variation of tree-ring widths of Scots pine (Pinus sylvestris L.) affected by air pollution

Abstract: Using eight populations of Scots pine growing in foothills of the Sudetes (southern Poland) as an example, the character and causes of annual ring variation in 1900-1999 were studied. The climate had a short-term effect on radial growth during the whole period investigated. A long-term decrease of radial growth occurred after 1960, but only in some localities. It was probably caused by non-climatic factors, most likely by industrial pollution. The decline of trees during that period is mainly evidenced by a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 14 publications
1
34
0
1
Order By: Relevance
“…Scientific literature reviews show, that the industrial pollutants usually have a negative impact on vitality and annual radial growth of trees. The strength of the negative impact of pollution on trees can be varied in space and depends on the habitat conditions and distance from the source of pollution, directions of prevailing winds (Wilczyński, 2006;Danek, 2007;Elling et al, 2009;Malik et al, 2012). The trees, growing under stress of the pollutants, reduce their radial growth and height growth (Kienast, 1985, Schweingruber, 1986Krąpiec and Szychowska-Krapiec, 2001;Danek, 2007;Elling et al, 2009;Malik et al, 2012;Crecente-Campo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Scientific literature reviews show, that the industrial pollutants usually have a negative impact on vitality and annual radial growth of trees. The strength of the negative impact of pollution on trees can be varied in space and depends on the habitat conditions and distance from the source of pollution, directions of prevailing winds (Wilczyński, 2006;Danek, 2007;Elling et al, 2009;Malik et al, 2012). The trees, growing under stress of the pollutants, reduce their radial growth and height growth (Kienast, 1985, Schweingruber, 1986Krąpiec and Szychowska-Krapiec, 2001;Danek, 2007;Elling et al, 2009;Malik et al, 2012;Crecente-Campo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Scientific literature reviews have shown that, the size of reduction also depends on the distance from the source of pollution, directions prevailing winds and area orography (Krąpiec and Szychowska Krąpiec, 2001;Juknys et al, 2003Juknys et al, , 2014Wilczyński, 2006;Elling et al, 2009;Malik et al, 2012;Rydval and Wilson, 2012;Bošela et al, 2014).…”
Section: Trees As Bio-indicatorsmentioning
confidence: 99%
“…The size of the ring is treated as a measure of vitality of the trees and their incremental potential (Swetnam and Lynch, 1993;Pedersen, 1998;Krause et al, 2003). In the absence of information about immisions, data on emissions of various pollutants are used (Krąpiec and Szychowska-Krąpiec, 2001;Wilczyński, 2006;Danek, 2007;Elling et al, 2009;Malik et al, 2012). (Na, Mg, Fe, Ni, Cu, Zn, Pb) in pine wood from area nearby chemical factories.…”
Section: Dendrochronological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although alternatives have been proposed (e.g., Vanclay and Henry 1988;Vanclay 1989), height-based SI remains one of the preferred methods for assessing site productivity in mixed-species stands (Vanclay 1992), notwithstanding the challenges of estimation. SI equations have been produced for many important temperate forestry species (Alemdag 1988;Brown 2006;Elfving and Kiviste 1997;Wilczynski and Slawomir 2006) but are lacking for most tropical species (Pancel 1993). Here, we aimed to determine SI equations for a selection of Australian tree species at contrasting sites in context of the main variables determining the growth of mixed species tree plantations in tropical Queensland.…”
mentioning
confidence: 99%